Clarithromycin: overview and its current clinical utility in the treatment of respiratory tract infections - Naik, Prashant; Prabhat, Divya; Shrivastava, Rakesh; Nair, Arun; Khandke, Devendra A. (International Journal of Research in Medical Sciences, 2024)
Upper respiratory tract infection (URTI) is a common reason for medical consultation all over the world. Streptococcus A (Strep A) and other infections can cause sore throat as well as pharyngitis or tonsillitis. It may also result in post-infection sequelae, including acute post-streptococcal glomerulonephritis, acute rheumatic fever, and rheumatic heart disease. As a result, there is a need for an antibiotic that is effective, easy to administer, has a favorable sensitivity pattern, and preferably has some additional pharmacodynamic properties that complement the basic antibacterial profile. Clarithromycin is a macrolide antibacterial agent with broad-spectrum activity against respiratory pathogens. It is especially active against atypical Chlamydia pneumoniae, Mycoplasma pneumoniae, and Legionella spp. It is well absorbed and stable at gastric pH. It is metabolized by the cytochrome P450 enzymes and forms 14-hydroxy clarithromycin, which is more active than the parent compound, especially against Hemophilus influenzae. It acts by preventing protein synthesis by binding to the 50S subunit of bacterial ribosomes. In dosages of 500 to 1000 mg/day for 5 to 14 days, clarithromycin is effective in the treatment of community-acquired upper and lower respiratory tract infections in hospital and community settings. It exerts significant anti-inflammatory, immunomodulatory, and post-antibiotic effects. It provides a viable option for the treatment of community-acquired respiratory tract infections, in both children and adults.